Protection of marine biodiversity from pollution: Legal strategies in Malaysia. - Mustafa, Maizatun; Ho Nyuk Onn @ Ariffin, Mariani (IACSIT Press, 2011)
This paper discusses sources of marine pollution in Malaysia and examines existing provisions under the law relevant to the control of such pollution. Being a maritime nation as well as one of the top biodiversity-rich countries in the world, it is important for Malaysia to give its full commitment in conserving her mega-diverse ecosystems, including that of the richly endowed seas. At present, the well being of Malaysia’s marine biodiversity is facing increasing threat from various sources, notably that of land-based and vessel-based pollution. Malaysia takes pollution issue seriously, and joins other key maritime nations in enhancing her legal regime in dealing with marine pollution. This paper seeks to highlight Malaysia’s continuous effort towards marine pollution control through the application of both domestic and international law. Significantly, such effort can be used as a reference by other maritime nations for the purpose of collective marine environmental protection and biodiversity conservation.